The annealing influence onto the electrical and magnetic behavior of magnetoresistive/insulator system - Ahmed, A.M.; Mohamed, Abd El-Mo’ez A.; Mohamed, H.F.; Diab, A.K.; Mohamed, Aml M.; Mazen, A.E.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
This investigation is mainly concerned with the effect of annealing temperature (600, 700, 800 and 900 °C) in air for (La0.7Ba0.3MnO3)1–x/(NiO)x with x = 0 and x = 0.10 samples. It was shown that the annealing temperature does not affect the structure and parameters of rhombohedral lattice of the samples. However, it is observed that the annealing treatment has a notable effect on the electrical resistivity and the metal-semiconductor transition temperature Tms. Temperature dependent magnetization measurements showed a decrease in Curie temperature TC with annealing temperature. In the same time, annealing process decreases the magnetoresistance of La0.7Ba0.3MnO3, in contrast to (La0.7Ba0.3MnO3)0.9/(NiO)0.1 composite.